Content popularity difference-aware cache eviction scheme for CDN-P2P hybrid networks - Hua NIE; Min ZHANG; Jing-rong GUO; Xiao-long YANG (Tongxin xuebao)
In CDN-P2P hybrid network,it is important for the cache eviction schemes to improve the delivery efficiency of content.However,most of them only consider the holistic popularity of content file,and neglect the difference between the individual popularities of segments within a content file.Hence,it was difficult to improve the hit rate of pre-cached content segments,and to reduce the user access delay.Hence based on the difference between the attributes of content popularity,a new cache eviction scheme (i.e.,Diff-Attribute) was proposed.Bewildered the holistic popularity of a content file,it also considered the individual popularity of its segment.More importantly,based on the concept of entropy,A method to measure the popularity difference between content files or segments was put forward.If the popularities of the segments within a content file are equalizing,its prefix segment would be pre-cached.Otherwise,the requested segments or files directly based on its popularity would be cached.Compared with traditional schemes (e.g.,LFU,LRU,MRU,FIFO),the simulation results show that Diff-Attribute can improve the cache hit rate and the byte hit rate by at least 6%,8% respectively,and can reduce the access startup delay rate and the transmission cost rate by at least 13%,7% respectively.